An Efficient, Stable and Reusable Palladium Nanocatalyst: Chemoselective Reduction of Aldehydes with Molecular Hydrogen in Water. Issue 10 (3rd May 2016) - Kotha, Surya Srinivas; Sharma, Nidhi; Sekar, Govindasamy
Abstract: Palladium nanoparticles (Pd‐BNP) stabilized by a binaphthyl‐backbone can be efficiently used for the chemoselective reduction of aldehydes in the presence of hydrogen at room temperature in water. The Pd‐BNP catalyst is easily recovered and reused for five catalytic cycles. Abstract :